New approaches to the synthesis of anisotropic, core-shell and hollow metal nanostructures - Sastry, M.; Swami, A.; Mandal, Sujata; Selvakannan, P. R. (Journal of Materials Chemistry, 2005)
The synthesis of nanomaterials with control over size, shape and chemical composition continues to be a major challenge in nanoscience. The requirements of nanomaterial synthesis are becoming more sophisticated and, in addition to anisotropic structures, there is much excitement surrounding the development of recipes for the synthesis of core-shell and hollow nanostructures. Much of the motivation for research in this direction stems from the unusual optoelectronic and chemical properties exhibited by such nanostructures. In this article, we review the work from this laboratory on the synthesis of flat gold nanostructures at the air-water interface, either by confining the reductant or the precursor metal ions to the air-water interface. We also describe the synthesis of phase-pure core-shell nanoparticles by immobilizing UV- and pH-dependent reducing agents on the surface of the core nanoparticles as well as the synthesis of organically soluble hollow-shell nanostructures via transmetallation reactions.